2016
DOI: 10.1080/09583157.2016.1234584
|View full text |Cite
|
Sign up to set email alerts
|

Potential of endophytic Streptomyces spp. for biocontrol of Fusarium root rot disease and growth promotion of tomato seedlings

Abstract: OATAO is an open access repository that collects the work of some Toulouse researchers and makes it freely available over the web where possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(38 citation statements)
references
References 29 publications
4
34
0
Order By: Relevance
“…In non-autoclaved soil, the native microorganisms showed a synergic effect in the biocontrol of R. solani. These findings are in agreement with those of Goudjal et al (2014Goudjal et al ( , 2016 in the biocontrol soil-borne phytopathogenic fungi, who suggest the presence of indigenous antagonistic microbes.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In non-autoclaved soil, the native microorganisms showed a synergic effect in the biocontrol of R. solani. These findings are in agreement with those of Goudjal et al (2014Goudjal et al ( , 2016 in the biocontrol soil-borne phytopathogenic fungi, who suggest the presence of indigenous antagonistic microbes.…”
Section: Discussionsupporting
confidence: 90%
“…However, it failed to grow using iron phosphate. These results are supported by those of Goudjal, Zamoum, Sabaou, Mathieu, and Zitouni (2016) and Liu et al (2014), who reported low activities of Streptomyces species in the solubilisation of iron phosphate. Hamdali et al (2008) studied the capacity of phosphate-solubilising actinobacteria to promote the growth of wheat plants.…”
Section: Discussionsupporting
confidence: 85%
“…It has also been documented that most Streptomyces species produce siderophores with diverse structural backgrounds [53]. Moreover, siderophore production is one of the mechanisms by which Streptomyces can exert beneficial effects on plant growth [71].…”
Section: Biosynthesis Of Factors Stimulating Plant Growthmentioning
confidence: 99%
“…Bioactive actinobacteria from indigenous Moroccan habitats were reported before (Barakate et al, ; Baz, Lahbabi, et al, ; Baz, Tran, et al, ; Hamdali et al, ; Samri et al, ). Many studies focused on the role of actinobacteria as biocontrol agents against a large number of phytopathogens (Costa, Zucchi, & Melo, ; Goudjal et al, ; Shrivastava, Kumar, & Yandigeri, ). However, no previous studies reported the use of actinobacteria against legume diseases caused by A. euteiches .…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 80% of the known commercial antibiotics used in medicine and agriculture have initially been isolated from actinobacteria, and especially from strains of genus Streptomyces (Sanglier, Haag, Huck, & Fehr, ), that proved to be a rich source of antibiotics. Furthermore, Streptomyces have been reported in several studies as biological control and showed potential to control a wide range of plant pathogenic bacteria, fungi and oomycetes by producing diverse bioactive substances (Baz, Lahbabi, et al, ; Baz, Tran, et al, ; Errakhi, Lebrihi, & Barakate, ; Goudjal, Zamoum, Sabaou, Mathieu, & Zitouni, ; Samri et al, ). These bacteria like many other microorganisms can also promote plant growth by producing phytohormones (Goudjal et al, ), by improved phosphate mobilization (Hamdali, Hafidi, Virolle, & Ouhdouch, ) and by production of siderophores for iron acquisition (Macagnan, Romeiro, Pomella, & Souza, ).…”
Section: Introductionmentioning
confidence: 99%